1999
DOI: 10.1001/archpedi.153.7.675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soy-Based Formulas With Lactose and With Sucrose in the Treatment of Acute Diarrhea in Infants

Abstract: To evaluate the effect of feeding infants a soybased formula with lactose compared with a soy-based formula with sucrose during an acute diarrheal episode. Participants and Methods: Two hundred boys, aged 3 to 18 months, who were admitted to the hospital with acute diarrhea and signs of dehydration were randomly assigned to receive a soy-based formula with lactose or sucrose after initial rehydration. Intake and output (stool, urine, and vomit) were measured and recorded every 3 hours until diarrhea resolved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The occurrence of spit-up/vomit was consistently lower throughout the study in the NoLAC group versus LAC group (P = .056 at 14 days and P = .02 at 112 days of age). This is consistent with reduced spit-ups noted with lactose-free soy protein-based formulas 25,26 and a lactose-free rice protein-based formula. 27 The NoLAC feeding produced a significantly greater proportion of softer stools and a lesser proportion of hard stools compared with the LAC feeding ( Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…The occurrence of spit-up/vomit was consistently lower throughout the study in the NoLAC group versus LAC group (P = .056 at 14 days and P = .02 at 112 days of age). This is consistent with reduced spit-ups noted with lactose-free soy protein-based formulas 25,26 and a lactose-free rice protein-based formula. 27 The NoLAC feeding produced a significantly greater proportion of softer stools and a lesser proportion of hard stools compared with the LAC feeding ( Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…[36][37][38] A systematic review published in 1994 found some evidence that lactose avoidance improved important clinical outcomes for young children with acute diarrhea, especially for children who were severely dehydrated because of the acute diarrheal illness. 17 Of the five subsequent RCT, [39][40][41][42][43] three found that lactose-free feeds significantly reduced the duration of diarrhea compared with feeds containing lactose. 39,42,43 The other two RCT found no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies compared cow’s milk or cow’s milk-based formula with soy-based, casein-based or whey-based formulas [16,23,31-34], one study compared regular milk to milk in which at least 95% of the lactose had been hydrolyzed [35], and one study compared soy-based formulas with and without added lactose [36]. Three studies allowed non-milk complementary foods in addition to the intervention and control liquid feeds, with complementary foods given identically across comparison groups [16,32,36]. All studies excluded severely malnourished children.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled result from five studies [16,31,32,35,36] showed a statistically significant effect of lactose-free liquid feeds on reducing diarrhea duration (SMD: -0.36; 95%CI: -0.62 to -0.10; p=0.008) (Table 3). Effect sizes and their statistical significance varied across studies but were consistent in direction (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation